Ultrasensitive quantification of the CYP2E1 probe chlorzoxazone and its main metabolite 6-hydroxychlorzoxazone in human plasma using ultra performance liquid chromatography coupled to tandem mass spectrometry after chlorzoxazone microdosing - Witt, Lukas; Hohmann, Nicolas; Mikus, Gerd; Haefeli, Walter E.; Burhenne, Jürgen (Journal of chromatography, 2016)
Chlorzoxazone is a probe drug to assess cytochrome P450 (CYP) 2E1 activity (phenotyping). If the pharmacokinetics of the probe drug is linear, pharmacologically ineffective doses are sufficient for the purpose of phenotyping and adverse effects can thus be avoided. For this reason, we developed and validated an assay for the ultrasensitive quantification of chlorzoxazone and 6-hydroxychlorzoxazone in human plasma. Plasma (0.5 mL) and liquid/liquid partitioning were used for sample preparation. Extraction recoveries ranged between 76 and 93% for both analytes. Extracts were separated within 3 min on a Waters BEH C18 Shield 1.7 μm UPLC column with a fast gradient consisting of aqueous formic acid and acetonitrile. Quantification was achieved using internal standards labeled with deuterium or 13C and tandem mass spectrometry in the multiple reaction monitoring mode using negative electrospray ionization, which yielded lower limits of quantification of 2.5 pg mL−1, while maintaining a precision always below 15%. The calibrated concentration ranges were linear for both analytes (2.5-1000 pg mL−1) with correlation coefficients of >0.99. Within-batch and batch-to-batch precision in the calibrated ranges for both analytes were <15% and <11% and plasma matrix effects always were below 50%. The assay was successfully applied to assess the pharmacokinetics of chlorzoxazone in two human volunteers after administration of single oral doses (2.5-5000 μg). This ultrasensitive assay allowed the determination of chlorzoxazone pharmacokinetics for 8 h after microdosing of 25 μg chlorzoxazone.